Khadimah dan Representasi Perempuan Salehah dalam Novel Bidadari Bermata Bening Karya Habiburrahman El Shirazy - Abdullah, Varatisha Anjani; Ashivah Misbah, Nuril (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2022)
The following article deliberates the construction of virtuous woman in Bidadari Bermata Bening, a novel by Habiburrahman El-Shirazy, as an Islamic literature which carries out a religious proselytizing mission. The evolution of Islamic literature in Indonesia post-reformation had open a new space of aspiration for its Muslim community. Particularly for FLP (Forum Lingkar Pena) writers’ community, this democratic-space is utilised as an entertaining propagation of Islam (dakwah-tainment) which mixes Islamic values and melodramatic romance. Furthermore, this article looks into the moral notion applied to characterise virtuous woman. The analysis was performed using Critical Discourse Analysis method. Critical approach was necessary to deconstruct the discourse built by author as an effort to develop knowledge through linguistic medium which then serves as veracity for the readers. Assisted by Islamic gender theories from Muslim feminists, this article exposes Islamic discourse that defines virtuous women through literature. Analysis result showed that a woman’s piety is not identified by common Islamic attributes such as veil and habitual act of worships, but also by the quality of service resembling a servant (khadimah) to her master (a man). The biggest service of a khadimah is giving her purity, virginity and her loyalty in love to the Master, which reinforces patriarchy value, male superiority, and inequality between men and women.